2015
DOI: 10.1155/2015/159625
|View full text |Cite
|
Sign up to set email alerts
|

Oral Streptococci Biofilm Formation on Different Implant Surface Topographies

Abstract: The establishment of the subgingival microbiota is dependent on successive colonization of the implant surface by bacterial species. Different implant surface topographies could influence the bacterial adsorption and therefore jeopardize the implant survival. This study evaluated the biofilm formation capacity of five oral streptococci species on two titanium surface topographies. In vitro biofilm formation was induced on 30 titanium discs divided in two groups: sandblasted acid-etched (SAE- n = 15) and as-mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 25 publications
3
32
0
Order By: Relevance
“…A similar morphological structure has been shown in previous studies evaluating biofilm formation on titanium discs (Bermejo et al, ; Cavalcanti et al, ; Sanchez et al, ). Similar to our results, no structural differences in the biofilm were identified when comparing discs with different titanium surfaces (Di Giulio et al, ; Ferreira Ribeiro et al, ; Pita et al, ; Scarano, Piattelli, Caputi, Favero, & Piattelli, ; Schmidlin et al, ).However, this investigation demonstrated that moderate‐roughness surfaces showed a higher number of bacteria within their characteristic pores. Similar morphological differences were also reported using SEM by Ferreira Ribeiro et al () in an in vivo investigation assessing the initial bacterial adhesion on titanium discs with different surface micro‐topography (Ferreira Ribeiro et al, ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A similar morphological structure has been shown in previous studies evaluating biofilm formation on titanium discs (Bermejo et al, ; Cavalcanti et al, ; Sanchez et al, ). Similar to our results, no structural differences in the biofilm were identified when comparing discs with different titanium surfaces (Di Giulio et al, ; Ferreira Ribeiro et al, ; Pita et al, ; Scarano, Piattelli, Caputi, Favero, & Piattelli, ; Schmidlin et al, ).However, this investigation demonstrated that moderate‐roughness surfaces showed a higher number of bacteria within their characteristic pores. Similar morphological differences were also reported using SEM by Ferreira Ribeiro et al () in an in vivo investigation assessing the initial bacterial adhesion on titanium discs with different surface micro‐topography (Ferreira Ribeiro et al, ).…”
Section: Discussionsupporting
confidence: 90%
“…Different in vivo (Al‐Ahmad et al, , ; de Melo, do Nascimento, Souza, & de Albuquerque, ; Ferreira Ribeiro et al, ; Groessner‐Schreiber, Hannig, Duck, Griepentrog, & Wenderoth, ; John, Becker, & Schwarz, , ; Xing, Lyngstadaas, Ellingsen, Taxt‐Lamolle, & Haugen, ; Zaugg et al, ) and in vitro (Badihi Hauslich, Sela, Steinberg, Rosen, & Kohavi, ; Di Giulio et al, ; Drake, Paul, & Keller, ; Montelongo‐Jauregui, Srinivasan, Ramasubramanian, & Lopez‐Ribot, ; Pita et al, ; Sanchez et al, ; Schmidlin et al, ; Violant, Galofre, Nart, & Teles, ) investigations have studied the impact of implant surface characteristics on biofilm formation, demonstrating that the physic‐chemical characteristics of the surface, mainly its roughness, significantly affected early bacterial colonization, biofilm formation and maturation(Burgers et al, ; Teughels et al, ). However, most of these studies have not used dental implants, but rather specimens, such as discs or slabs made of the implant surfaces, but without taking into account the implant macroscopic and topographic characteristics, such as the threads and the inter‐thread concavities.…”
Section: Introductionmentioning
confidence: 99%
“…Pita et al studied the behavior to form biofilm of five oral streptococci species on various dental implant surface topographies. Their data showed that S. cricetus , S. mutans , and S. sobrinus exhibited higher biofilm formation compared to S. salivarius and S. sanguinis , suggesting that biofilm formation depends on not only the surface topography but also the bacteria species involved [43]. Similarly, Mei et al [44] reported that although both S. sanguinis and S. mutans were sensitive to changes in surface roughness, the initial adhesion forces of the former, initial colonizer, were more affected.…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro research on implant surfaces has shown that roughness, surface free energy, wettability, and degree of sterilization may affect biofilm formation, bacterial three-dimensional distribution, and antimicrobial treatment efficacy (Al-Ahmad et al, 2010;Di Giulio et al, 2016;Lin, Liu, Wismeijer, Crielaard, & Deng, 2013;Schmidlin et al, 2013;Song et al, 2015;Yeo, Kim, Lim, & Han, 2012). These studies have used specimens, such as disks or slabs containing the studied surface (Aguayo, Donos, Spratt, & Bozec, 2015;de Avila et al, 2015;Di Giulio et al, 2016;Papavasileiou, Behr, Gosau, Gerlach, & Buergers, 2015;Pita et al, 2015;Ready et al, 2015), but these specimens lack the macro-structural and topographic characteristics of the dental implants used clinical practice. Furthermore, many of these in vitro investigations assessing bacterial adhesion and colonization on implant surfaces have used simple biofilm models, consisting of one or, maximum, two bacterial species, and/ or have used short-term evaluations (24 hr or less), thus, lacking the ability to properly study the dynamics of the biofilm maturation and its potential pathogenicity (Pereira et al, 2015;Schmidt et al, 2017;Sridhar et al, 2016).…”
mentioning
confidence: 99%